A rare neurosurgical emergency: case report of spontaneous lumbar subdural empyema - Svetozar Stanković; Milan Lepić; Ivan Bogićević; Jadranka Stanković; Goran Pavlicević (Egyptian Journal of Neurosurgery)
Abstract Background Spinal subdural empyema (SDE) is a rare but serious infection that can lead to severe neurological deficits if not diagnosed and managed promptly. This case report presents a rare instance of spontaneous SDE and discusses the management approach, highlighting the importance of early diagnosis and intervention. Case presentation A 52-year-old male presented with acute-onset lumbar pain without radicular symptoms. Initial lumbar spine computed tomography was unremarkable, leading to home-based analgesic and steroid therapy. The patient’s condition deteriorated, developing severe radicular pain, high-grade fever, and signs of sepsis within seven days. Laboratory tests showed elevated inflammatory markers. Contrast-enhanced magnetic resonance imaging (MRI) revealed lumbar SDE at the L3-L5 levels. Emergency surgical intervention, including wide laminectomy and subdural space irrigation, was performed. Postoperatively, the patient received broad-spectrum antibiotics followed by targeted antibiotic therapy based on culture results. The patient showed significant clinical improvement post-surgery. Initial broad-spectrum antibiotic therapy was followed by targeted therapy (vancomycin and levofloxacin) for three weeks, and then oral cephalosporins for four weeks. Laboratory parameters normalized, and the patient reported pain relief with no symptom relapses over six months. Conclusion Spinal SDE, though rare, should be considered in patients with acute lumbar pain syndrome, particularly when associated with signs of infection. Early diagnosis and prompt surgical intervention combined with appropriate antibiotic therapy are crucial for favorable outcomes. This case highlights the need for urgent MRI in the early stages of symptom onset to ensure timely diagnosis and treatment.